Addendum to the preliminary report on Operation Tundra. (1943)
Addendum report of encounter with Russian submarine. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, Reel 1621, 210 Infantry Division, folder 45787/3, first frame 000552. Translated by Major James F. Gebhardt, USA (retired)